PERSPECTIVES ON EDUCATION IN TODAY'S WORLD AND TOMORROW'S: INSIGHTS FROM 'DOWN UNDER' (International Journal of Food and Nutritional Sciences, 2021)
This study examines philosophy of education from an Australasian viewpoint, focusing on both current and future developments in the field. Although there are many international connections in this region of the globe for educational philosophy, there are no native influences. Many philosophical movements have emerged, such as naturalism and postmodernism, which have influenced ideas about practice and policy in education. Philosophers been promoted to professorial posts within the institutional side of philosophy of education, but their numbers have been steadily declining as they leave without being replaced. The survival of an academic community, the ability to teach papers in the field to undergraduate and graduate students (and thereby replace ourselves), and persuading educators and decision-makers that philosophy of education plays a critical role in enhancing both policy and student educational experiences will determine how well philosophy of education does in the future.